Auditing private companies: what do we know?/Ann Vanstraelen, Caren Schelleman. - Vanstraelen, Ann.
The purpose of this article is to provide an overview of the literature on what we currently know about the costs and benefits of auditing private company accounts. Our main conclusions are the following. First, there is much heterogeneity in factors driving audit demand in private companies and the value derived from the audit. Second, research provides support for improved financial reporting quality due to, and real economic benefits from, private company audits. Third, the cost–benefit analysis for private company audits is firm-specific and mandating the audit does not seem to be cost-effective and thus economically optimal for all private companies. Alternative services may better meet the needs of especially smaller private companies. Furthermore, mandating the audit is not necessarily an optimal solution since private companies with low demand for a high-quality audit are able to find an auditor that meets their requirements even under a mandatory regime. Hence, having a mandatory audit in place is no guarantee for universally high-quality audits and this seems most salient for private companies where auditors may be more prone to independence issues. We conclude by providing a number of directions for future research.